PENYULUHAN DAN PELATIHAN PENGOLAHAN LIMBAH TERNAK KAMBING MENJADI PUPUK DI KELOMPOK TERNAK KARYA MANDIRI - Zulkarnain, Zulkarnain (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Goat waste is beneficial for farmers as organic fertilizer. Processing goat waste into organic fertilizer significantly reduces the use of chemical fertilizers in agriculture. This is what the Karya Mandiri Livestock Group is leveraging to continue producing organic fertilizer, amidst the ever-increasing demand. The Karya Mandiri Livestock Group faces challenges related to improved production and the equipment used is still very rudimentary. Therefore, empowerment is needed to further advance the group, especially in organic fertilizer production. The Karya Mandiri Livestock Group has 15 members located in Bandar Sakti Village, Terbanggi Besar District, Central Lampung Regency. The community service program is divided into three stages: Focus Group Discussion (FGD), Counseling, and Training.